Knave of diamonds [large type] - King, Laurie R. (King, Laurie R. Mary Russell novel., 2025)
"When Mary Russell was a child, she adored her Uncle Jake. But she hasn't heard from him in years--until her presents himself at her door. He was involved in a disappearance of the Irish Crown Jewels, a theft that baffled Sherlock Holmes himself. And now Jake expects Russell to slip away with him, not telling Holmes what she's up to. Siding with her uncle could only place her in opposition to her husband-partner. On the other hand, this is her childhood hero. Conflicting loyalties and international secrets, lies and deceptions: sounds like a case for Mary Russell and Sherlock Holmes"--